2020
DOI: 10.1002/cld.873
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathogenesis of Autoimmune Hepatitis†

David N. Assis

Abstract: http://aasldpubs.onlinelibrary.wiley.com/hub/journal/10.1002/(ISSN)2046-2484/video/15-3-reading-assis a video presentation of this article http://aasldpubs.onlinelibrary.wiley.com/hub/journal/10.1002/(ISSN)2046-2484/video/15-3-interview-assis the interview with the author

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Various cytokines have been reported to participate in the pathogenesis of AIH. Th1 cytokine induce macrophage and T-cell activation, Th2 cytokine induce the production of autoantibodies and Th17 cytokines produce pro-inflammatory cytokines, all of which ultimately contribute to hepatocyte necroinflammation [1]. One previous in vivo study demonstrated that RAGE activation was responsible for the Th1 cell activation and cytokine production in pathogenesis of autoimmune response [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various cytokines have been reported to participate in the pathogenesis of AIH. Th1 cytokine induce macrophage and T-cell activation, Th2 cytokine induce the production of autoantibodies and Th17 cytokines produce pro-inflammatory cytokines, all of which ultimately contribute to hepatocyte necroinflammation [1]. One previous in vivo study demonstrated that RAGE activation was responsible for the Th1 cell activation and cytokine production in pathogenesis of autoimmune response [15].…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune hepatitis (AIH) is a liver-specific autoimmune disease characterized by hypergammaglobulinemia, increased circulating autoantibodies, transaminases, and histological evidence of interface hepatitis [1]. AIH occurs in all ethnicities and ages, with a female predominance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, a significant decrease in numerous peripheral cytokine levels (IL-6, IL-8, IL-10, IL17 and IL-23) was detected at the conclusion of the 8-week MBSR course compared to baseline. These reductions are potentially interesting given the association of IL-10, and IL-6 and IL-23/IL-17, with disease pathophysiology in AIH through promotion of pathogenic B-cell and effector T-cell responses, respectively 1,33,34 . A better understanding of the relationship between these peripheral cytokine levels and AIH disease activity in the context of stress reduction through MBSR remains to be determined through future studies.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…The pathogenesis of AIH is complex and involves interactions between tolerant liver, environmental triggers, and dysregulated immunological mechanisms. Genetic factors influence an individual’s susceptibility to developing AIH 1 , 2 .…”
Section: Introductionmentioning
confidence: 99%